(untitled) (Ameghiniana, 2017)
The earliest records of the genus Spiticeras Uhlig in Western Gondwana occur in the Upper Jurassic–Lower Cretaceous deposits of the Vaca Muerta Formation in the Neuquén Basin, Argentina. Those records involve two species, Spiticeras acutum Gerth and Spiticeras hauthali Gerth, which were firstly described from Arroyo Durazno, Mendoza. A systematic revision and reconsideration of the biostratigraphic distribution of both species was performed based on the study of type material and new bed-by-bed collections in the type locality and other southern Mendoza sections. S. acutum and S. hauthali display a succession of ornamentation stages that, together with other morphological characters, sustain their assignation to the genus Spiticeras. Addidionally, macroconchiate and microconchiate specimens were identified in both taxa. The record of S. acutum from the lowermost beds assigned to the Late Tithonian–Early Berrisian Substeueroceras koeneni Assemblage Biozone substantiates the downwards extension of the known range of the species in the Neuquén Basin. Given that the basal portion of the S. koeneni Biozone can be correlated with the Late Tithonian Standard “Durangites” Zone and that these early spiticeratins records have been found to be associated with a Late Tithonian secondary nannofossil bioevent (Raghodiscus asper (Stradner) first occurrence) in two of the studied sections, a Late Tithonian age is suggested for the earliest records of Spiticeras in Gondwana. Resumen. LOS REGISTROS MÁS TEMPRANOS DEL GÉNERO SPITICERAS UHLIG EN LA CUENCA NEUQUINA, ARGENTINA: IMPLICACIONES SISTEMÁTICAS Y BIOESTRATIGRÁFICAS. Los registros más tempranos del género Spiticeras Uhlig en Gondwana Occidental se encuentran en los depósitos del Jurásico Tardío–Cretácico Temprano de la Formación Vaca Muerta en la Cuenca Neuquina, Argentina. Esos registros comprenden a dos especies, Spiticeras acutum Gerth y Spiticeras hauthali Gerth, descriptas originalmente de Arroyo Durazno, Mendoza. Se llevó a cabo una revisión sistemática y una reconsideración de la distribución bioestratigráfica de ambas especies sobre la base del estudio del material tipo y de nuevas colecciones realizadas estrato a estrato en la localidad tipo y en otras secciones del sur de Mendoza. Se ha probado que S. acutum y S. hauthali exhiben una sucesión de estadios de ornamentación que, junto con otros caracteres morfológicos, fundamentan su asignación al género Spiticeras. Se identificaron además macroconchas y microconchas para ambos taxa. El registro de S. acutum desde niveles basales asignados a la Biozona de Asociación de Substeueroceras koeneni del Tithoniano Tardío–Berriasiano Temprano, permite extender el límite inferior del rango conocido de la especie en la Cuenca Neuquina. Dado que la porción basal de la Biozona de S. koeneni puede ser correlacionada con la Zona Estándar de “Durangites” del Tithoniano Tardío, y que estos registros tempranos de espiticeratinos han sido hallados en conexión con un bioevento secundario registrado en nanofósiles del Tithoniano Tardío (la primera aparición de Rhagodiscus asper (Stradner)) en dos de las secciones estudiadas, se sugiere una edad tithoniana tardía para los primeros registros de Spiticeras en Gondwana.